2018
DOI: 10.1155/2018/1736957
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mechanical Properties of the Human Tympanic Membrane and Its Influence on the Dynamic Behaviour of the Human Hearing System

Abstract: The difficulty to estimate the mechanical properties of the tympanic membrane (TM) is a limitation to understand the sound transmission mechanism. In this paper, based on finite element calculations, the sensitivity of the human hearing system to these properties is evaluated. The parameters that define the bending stiffness properties of the membrane have been studied, specifically two key parameters: Young's modulus of the tympanic membrane and the thickness of the eardrum. Additionally, it has been complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…These higher values could be overestimated by the presence of tension in the tympanic membrane that is released when the static tests are performed. In a previous research we have shown how experimental data can fit numerical models with a huge combination of pre-strain and elastic modulus values [29], being very sensitive to small values of the pre-strain in accordance with the results shown in Figure 11. The presence of pre-strain in the tympanic membrane has been hypothesised since long time ago [36,37] and is a question under discussion in current hearing research.…”
Section: Eardrum Equivalent Membranesupporting
confidence: 87%
See 2 more Smart Citations
“…These higher values could be overestimated by the presence of tension in the tympanic membrane that is released when the static tests are performed. In a previous research we have shown how experimental data can fit numerical models with a huge combination of pre-strain and elastic modulus values [29], being very sensitive to small values of the pre-strain in accordance with the results shown in Figure 11. The presence of pre-strain in the tympanic membrane has been hypothesised since long time ago [36,37] and is a question under discussion in current hearing research.…”
Section: Eardrum Equivalent Membranesupporting
confidence: 87%
“…The mechanical properties of the material are: density 1200 kg/m 3 , Poisson's ratio 0.3 and Young's modulus (E) 32 MPa. These properties are commonly accepted as a good estimation for the human TM [29].…”
Section: Eardrum Equivalent Membranementioning
confidence: 99%
See 1 more Smart Citation
“…An additional effect could be the reduced tension of the pars tensa (PT) after perforation, which would lead to a less defined contact and make the countersurface more compliant. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…The tympanic membrane (TM) receives and converts soundpressure waves over a broad frequency spectrum from the external environment into mechanical vibrations, which are conducted through the ossicular chain resulting in movement of perilymph and neural transduction in the hair cells of cochlea (Decraemer et al, 1991;Caminos et al, 2018). Damage, perforation and degeneration of the TM due to injury, otitis media and aging are leading causes of hearing impairment and deafness, with obvious impacts on an individual's life quality.…”
Section: Introductionmentioning
confidence: 99%